DESIGN AND DEVELOPMENT OF A PERMANENT MOULD FOR CRUCIBLE PRODUCTION (Nigerian Journal of Technology, 2019)
This study aimed at development of a permanent mould for crucible production. Solid-Works was used as the computer aided design (CAD) tool for design and structural analysis of the parts, with necessary design considerations put in place. The fabrication of the mould was carried out at Federal Institute for Industrial Research Oshodi (FIIRO), selecting Mild steel as the parent material. The mould basically consisted of the male and female parts made up of medium carbon steel because of the required strength. It was discovered from the structural analysis that the application of 1.0783 MN/m2 to produce the crucible from the mould is safe because it is not up to the von-mises maximum pressure of similar load of 5.584 MN/m2, this is lesser than the yield strength of the material which is given to be 2.481 MN/mm2. This shows that the material and its specification is safe and will not fail for the purpose for which it is designed for. Results showing the displacement and strain analysis revealed that the displacement in the mould is in the rate of 0.001 MN/mm and 0.00173 mm. This displacement is insignificant to cause failure in the part. And the strain is seen to be in the range 2.176 X 10-8 and 2.232 X 10-5, the results therefore give confidence in the design to meet requirement.  http://dx.doi.org/10.4314/njt.v38i3.11